Simple and rapid spectrophotometric assay of albendazole in pharmaceuticals using iodine and picric acid as CT complexing agents - Nagaraju Swamy; Kanakapura Basavaiah (Universidade de São Paulo, 2014)
Two simple, rapid and inexpensive spectrophotometric methods are described for the determination of albendazole (ALB) in bulk drug and in tablets. The methods are based on charge-transfer (CT) complexation reaction involving ALB as n-donor and iodine as σ-acceptor (method A) in dichloromethane or picric acid (PA) as π-acceptor (method B) in chloroform. The absorbance of CT complexes was measured at 380 nm for method A, and 415 nm for method B. The optimization of the experimental conditions is described. Under optimum conditions, Beer's law obeyed over the concentration ranges 8.0-240 and 2.4-42 μg mL-1 for method A and method B, respectively. The apparent molar absorptivity of CT complexes at the respective λmax are calculated to be 1.17×103 and 5.22×103 L mol-1cm-1 respectively, and the corresponding Sandell sensitivity values are 0.2273 and 0.0509 ng cm-2. The limits of detection (LOD) and quantification (LOQ) are calculated to be (0.69 and 2.08), and (0.10 and 0.30) μg mL-1 with method A, and method B, respectively. The intra-day and inter-day accuracy expressed as % RE and precision expressed as % RSD were less than 3%. The methods were applied to the determination of ALB in tablets.